2015
DOI: 10.1111/cdoe.12161
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early childhood caries incidence among high caries‐risk children

Abstract: Objectives To assess the relationships between different behavioral factors and Early Childhood Caries (ECC) in African-American pre-school children. Methods Ninety-six African-American children aged 3 to 22 months old at baseline were recruited by word of mouth from Uniontown, Alabama, a non-fluoridated community. The children had dental examinations annually following World Health Organization (WHO) criteria at baseline, 1st, 2nd and 3rd follow-up. Parents provided detailed oral hygiene and dietary informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 21 publications
2
67
1
11
Order By: Relevance
“…We found that nearly all articles included non-White children. Some articles focused exclusively on minority children, including 20 that focused specifically on African American children (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71); 19 that focused on Hispanic children (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90); six that focused on Native American, Alaskan Native or American Indian children (91)(92)(93)(94)(95)(96); and one that focused on Asian or Asian-American children (97). These articles may serve as references to evaluators wishing to assess beverage consumption in these populations, although evaluators should attend to whether the assessment methods described in these articles have been ...…”
Section: Discussionmentioning
confidence: 99%
“…We found that nearly all articles included non-White children. Some articles focused exclusively on minority children, including 20 that focused specifically on African American children (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71); 19 that focused on Hispanic children (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90); six that focused on Native American, Alaskan Native or American Indian children (91)(92)(93)(94)(95)(96); and one that focused on Asian or Asian-American children (97). These articles may serve as references to evaluators wishing to assess beverage consumption in these populations, although evaluators should attend to whether the assessment methods described in these articles have been ...…”
Section: Discussionmentioning
confidence: 99%
“…This report involves secondary analyses of data from a longitudinal study conducted at the University of Alabama at Birmingham (UAB) [Ghazal et al, 2015]. A cohort of low socioeconomic status, African-American children was recruited in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Using an area-under-the-curve (AUC) composite, Ghazal et al [2015] previously assessed risk factors for dental caries experience longitudinally in this study's cohort and found that greater frequency of toothbrushing and greater daily frequency of consumption of 100% juices were associated with lower incidence of dental caries (p = 0.01 and 0.049, OR = 0.34 and 0.37, respectively). Greater daily frequency of consumption of sweetened foods (AUC composite) was associated with greater incidence of early childhood caries (OR = 9.22, p = 0.002).…”
mentioning
confidence: 99%
“…Teeth studied from different periods of man's history including those from 130,000 years ago, 1st century, 10th century and 20th century reported that the number of decayed teeth was 0%, 2%, 3% and 12% respectively [1]. In a study of Neolithic man (10,200 BC) in northern China carious lesions were reported in 6%, of teeth, however, the proportion of individuals with at least one carious tooth was 42% [2]. A study of caries in a more recent population (10th-15th centuries) in rural southwest France found the prevalence of caries as high as 17% [3].The rise in agriculture is often blamed for the increase in cavities due to widespread fermentable carbohydrates and bacteria that destroy tooth enamel [4].…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood caries is associated with nonfluoridated water, consumption of sugar dense foods, poor dental hygiene and irregular dental check-ups [10]. Unassisted tooth brushing in young children up to 6 years of age has been identified as a risk factor for caries development [11].…”
Section: Introductionmentioning
confidence: 99%